The City Moves West Economic and Industrial Growth in Central West Texas - Martin, Robert L. (University of Texas Press, 2021)
Where water supply, railway transportation, and oil reserves have been abundant, towns in central West Texas have prospered; where these resources are few, settlements have maintained only slight growth or disappeared entirely. Supporting his conclusions with profuse statistical evidence, Robert L. Martin traces the economic development of six major towns in the area, all with over 10,000 residents in 1960: Lamesa, Snyder, Sweetwater, Big Spring, Midland, and Odessa. Ranching brought the first settlers to West Texas in the 1870s and dominated the economy until 1900. In the 1880s farmers began to arrive, and between 1900 and 1930 agricultural production replaced ranching as the most important industry. With the influx of population came the railroad, and small settlements were established along its route. Those with sufficient water supply prospered and, as counties were organized, became county seats and supply centers for the surrounding agricultural regions. The land could not support a large agricultural population, and agriculture-related manufactures soon drew population to the towns. However, it was not until the oil discoveries of the 1920's that the modern city emerged. After World War II, oil production and oil-related industries generated great wealth and caused a boom in population growth and urban development. Despite the growth in prosperity, the economy is precariously balanced. Urban centers dependent on oil-an industry of limited life-have matured in an area without sufficient water or agricultural resources to support them. Martin concludes that, without careful planning and a solution to the water problem, these cities could some day become ghost towns on the plains